(untitled) - Charles, Muhirwa Safari (Can Tho, 2018)
This book introduce about produce families of 5th generation of red tilapia. Estimate genetic parameters for reproductive traits in red tilapia. Determine survival, fertility and hatching rate of red tilapia.
Keywords: Nuôi cá,Fish culture; Nghiên cứu,Research